Fluorine‐Free Bio‐Based Multifunctional Superhydrophobic Hyperbranched Self‐Cleaning Coating for Oil‐Water Separation. Issue 1 (9th November 2021) - Cao, Yang; Zhou, Meng; Fu, Heqing
Abstract: In this paper, first, UV‐curable vinyl‐terminated hyperbranched polyester (VTDP) is synthetized via a two‐step reaction. Then, mono‐sulfhydryl terminated polydimethylsiloxane (PDMS‐SH) is prepared via esterification reaction. Finally, cotton fabrics are immersed in mixtures of PDMS‐SH, double‐sulfhydryl terminated polydimethylsiloxane (HS‐PDMS‐SH), VTDP and hydrophobic fumed silica (HFS), and cross‐linking polydimethylsiloxane with hydrophobic fumed silica (HCPDMS@HFS) fabrics are prepared by 35 s of UV irradiation. When the content of HFS is 2.0 wt%, the superhydrophobic HCPDMS@HFS fabrics with high water contact angle (158.5) as well as low sliding angle (6.8) are obtained. At the same time, HCPDMS@HFS fabrics can withstand sandpaper abrasion for 30 cycles and tape‐peeling repetition for 100 times. They also exhibit excellent self‐cleaning ability, chemical durability, thermal stability, and good recyclability. Abstract : The cotton fabrics are immersed into a mixture of mono‐sulfhydryl‐terminated polydimethylsiloxane (PDMS‐SH), double‐sulfhydryl‐terminated polydimethylsiloxane (HS‐PDMS‐SH), vinyl‐terminated UV‐curable hyperbranched polyester (VTDP) and hydrophobic fumed silica (HFS), and the heavy cross‐linking polydimethylsiloxane with hydrophobic fumed silica (HCPDMS@HFS) fabrics are prepared. The HCPDMS@HFS fabrics have good hydrophobicity.